Anthropomorphism: In The Web of Culture - Fawcett, Leesa (UnderCurrents: Journal of Critical Environmental Studies, 1989)
As a conservationist and an environmental educator, I am intrigued by human relationships with animals. The umbrella question for me is in what ways do people relate to animals at this moment in Western history? I have focussed here on one type of relationship that humans have with animals – the anthropomorphic relationship.